Involvement of central cholinergic mechanisms in the effects of oxytocin and an oxytocin receptor antagonist on retention performance in mice - Boccia, Mariano Martín (2000)
Oxytocin (OT, 0.10 μg/kg, sc) impaired retention of a one-trial step-through inhibitory avoidance task when injected into male Swiss mice 10 min after training, as indicated by retention performance 48 h later. In contrast, the immediate post-training administration of the putative oxytocin receptor antagonist d(CH2)5[Tyr(Me)2, Thr4, Thy-NH2/9] OVT (AOT, 0.30/μg/kg, sc) significantly enhanced retention performance. Neither OT nor AOT affected response latencies in mice not given footshock on the training trial, and neither the impairing effects of OT nor the enhancing effects of AOT were seen when the training-treatment interval was 180 min, suggesting that both treatments influenced memory storage. The effects of OT (0.10 μg/kg, sc) on retention were prevented by AOT (0.03 μg/kg, sc) given immediately after training, but 10 min prior to OT treatment. The central acting anticholinesterase physostigmine (35, 70, or 150 μg/kg, ip), but not its quaternary analogue neostigmine (150 μg/kg, ip), reversed the impairment of retention performance induced by OT, whereas low subeffective doses of the centrally active muscarinic cholinergic antagonist atropine (0.5 mg/kg, ip) or the central acting nicotinic cholinergic antagonist mecamylamine (5 mg/kg, ip), but not methylatropine (0.5 mg/kg, ip) or hexamethonium (5 mg/kg, ip), prevented the enhancement of retention performance caused by AOT. We suggest that oxytocin negatively modulates the activity of central cholinergic mechanisms during the posttraining period that follows an aversively motivated learning experience, leading to an impairment of retention performance of the inhibitory avoidance response. (C) 2000 Academic Press.